USO DE MODELO DE TEORIA DAS FILAS NA GESTÃO PÚBLICA: A ESCOLA VOLTADA PARA O ALUNO: USE OF QUEUE THEORY MODEL IN PUBLIC MANAGEMENT: THE SCHOOL GEARED TOWARDS THE STUDENT - Gonçalves, Wellington; Santana Curto, Ramon; Reis Maciel, Euber; Machado Gambarine, Rosângela (Brazilian Journal of Production Engineering, 2020)
The queues are present in our daily lives, being one of the main factors that hinder the adequate service of the population, whether in private activities and, mainly in public services. Meeting the expectations and anxieties of users, in terms of public management, has not always received due attention. Within this context, schools have several processes and activities with recurring queues. Thus, the queuing problem negatively influences learning, even acting on the conduct of students. Considering these assumptions and, from the point of priority of solving activities with this potential, in this work, the process of forming queues to serve school lunches was analyzed. And from that, queue theory parameters in the school operating environment related to school meals were analyzed. The results suggest that the local conditions and the number of available servers were not sufficient to meet the demand and, therefore, at certain times employees had to travel to another point in this environment to conclude appointments, resulting in the expansion of the queue.